ELECTRONIC MEDICAL RECORD AT RSIGM SULTAN AGUNG SEMARANG REVIEWED FROM THE COMPLETENESS AND THE SAFETY FORMAT SYSTEM - Adam Reza Pahlevi; Erdianto Setya Wardhana; Erna Dwi Agustin (Faculty of Dentistry, Universitas Islam Sultan Agung, 2021)
Background: An electronic medical record is a medical system that can be used to store information about the track of a patient`s health. The completeness format of Electronic Medical Record used the format of Electronic Medical Record Guidance from Health Ministry Year 2015. The safety of electronic medical records has 6 aspects as follows privacy, integrity, authenticity, availability, access, control, non-rapadiatum.Method: This research aimed to know the description of the completeness format and the safety of The Electronic Medical Record at RSIGM Sultan Agung Semarang. This research used descriptive observational using a cross-sectional method. The subject of this study was Electronic Medical Records in March 2020. The samples were selected according to the inclusion criteria obtained from RSIGM Sultan Agung SemarangResult: The result of this research was used to know the description of the completeness of Electronic Medical Record Format and the safety of Electronic Medical Record at RSIGM Sultan Agung Semarang.Conclusion: The conclusion of this research showed Electronic Medical Record had been applied at RSIGM Sultan Agung Semarang but there are still lack in the informed consent form and the informed refusal, the safety of the electronic medical record was still lack in the electronic signature format.